Direct and indirect effects of psychological well-being and therapeutic alliance on therapy outcome in eating disorders - Muzi, Laura; Carone, Nicola; Mirabella, Marta; Franco, Anna; Rugo, Michele A.; Mazzeschi, Claudia; Lingiardi, Vittorio (Frontiers in Psychology, 2024)
Introduction: Outcome research in eating disorders (EDs) is commonly focused on psychopathological dysfunction. However, Ryff's model of psychological well-being (PWB) has shown promising-yet preliminary-results with ED patients. Additionally, despite substantial evidence highlighting the association between the therapeutic alliance and treatment outcome, findings in ED samples remain unclear. The present study aimed at exploring the direct effect of PWB dimensions and the early therapeutic alliance on ED patients' individual treatment responses, as well as the mediating role played by the early therapeutic alliance in the relationship between PWB dimensions and overall pre-post symptom change. Methods: A sample of N = 165 ED patients assigned female at birth, who were receiving treatment in a residential program, completed the Psychological Well-Being Scale at treatment intake and the Working Alliance Inventory after the first four psychotherapy sessions. Patients also completed the Outcome Questionnaire-45.2 at the same time point and during the week prior to discharge.The PWB dimensions of autonomy, positive relations, and self-acceptance were associated with clinically significant change, while the dimensions of personal growth and self-acceptance were associated with reliable change. The early therapeutic alliance showed both direct and indirect effects on therapy outcome, predicting clinically significant and reliable symptom reduction. It also emerged as a significant mediator in the relationship between all PWB dimensions and overall symptomatic change.The identification of individual, adaptive characteristics in ED patients that might influence their development of an early therapeutic alliance may help therapists to predict relationship ruptures and tailor their interventions to enhance treatment effectiveness.